การเลือกฝูงในปลาตะเพียนขาว (Barbonymus gonionotus) - Piyapong, Chantima; Tangsitthi, Krongthong (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2018)
Shoaling Preference in the Silver Barb (Barbonymus gonionotus) Chantima Piyapong and Krongthong Tangsitthi รับบทความ: 14 กุมภาพันธ์ 2561; ยอมรับตีพิมพ์: 28 พฤษภาคม 2561 บทคัดย่อ จากทฤษฎีคาดการณ์ว่าปลาจะเลือกอยู่กับฝูงจากพื้นฐานของการมีลักษณะภายนอกที่คล้ายคลึงกัน เพื่อลดความเสี่ยงต่อการถูกล่าและเพิ่มประสิทธิภาพในการหาอาหาร โดยทั่วไปปลาที่อยู่เป็นฝูงมีสมาชิกที่มีความคล้ายคลึงกันอย่างน้อยลักษณะใดลักษณะหนึ่งดังต่อไปนี้ เช่น ชนิด เพศ ฟีโนไทป์ ภาวะทางปรสิต ความคุ้นเคย ความเป็นเครือญาติ โดยศึกษาพฤติกรรมการเลือกฝูงโดยใช้การทดสอบแบบสองทางเลือก (binary choice) ในห้องปฏิบัติการของปลาตะเพียนขาวที่เป็นปลาทดสอบ (Barbonymus gonionotus) ระหว่างฝูงปลากระตุ้นชนิดเดียวกันและฝูงปลากระตุ้นต่างชนิดกัน ได้แก่ ปลานิล (Oreochromis niloticus) และปลายี่สกเทศ (Labeo rohita) ซึ่งตั้งสมมติฐานว่าปลาตะเพียนขาวจะเลือกฝูงปลาชนิดเดียวกันมากกว่าต่างชนิดกันและเลือกปลากระตุ้นในวงศ์เดียวกัน (ปลายี่สกเทศ) มากกว่าต่างวงศ์กัน (ปลานิล) ผลการศึกษาพบว่า ปลาตะเพียนขาวที่เป็นปลาทดสอบเลือกฝูงปลาที่เป็นชนิดเดียวกันมากกว่าต่างชนิดกันและเลือกฝูงปลาที่เป็นวงศ์เดียวกันมากกว่าต่างวงศ์กัน ซึ่งผลการศึกษานี้สอดคล้องกับทฤษฎีดังกล่าวข้างต้น คำสำคัญ: การเลือกฝูง ปลาตะเพียนขาว พฤติกรรม Abstract In theory, it predicts that fish should assort in shoals on the basis of similar phenotypic traits to minimize predation risk and to maximize foraging efficiency. In general, shoal members should have phenotypic assortments: such as species, sex, phenotype, parasitism, familiarity and kinship. By using binary choice test in the laboratory, shoaling preference of the silver barbs (Barbonymus gonionotus) as test fish was investigated. The silver barbs were given a choice of two stimulus shoals of the conspecifics/heterospecifics and of the heterospecifics (Nile tilapia (Oreochromis niloticus) or Rohu (Labeo rohita)). It was hypothesized that the test fish would prefer to shoal with the same family (Rohu) rather than to shoal with the different family (Nile tilapia). As predicted, it was found that the silver barbs as test fish preferred to shoal with the conspecific rather than heterospecific and they also preferred to shoal with the same family rather than to shoal with the different family. This finding supported the theory that fish preferred to associate with similar phenotypes. Keywords: Shoaling, Silver Barb, Behavior